2005
DOI: 10.1002/ijc.21262
|View full text |Cite
|
Sign up to set email alerts
|

High constant incidence rates of second cutaneous melanomas

Abstract: The incidence of most epithelial cancers rises with a power of age. However, second breast cancers have a high constant incidence independent of age. The skin is one of the few other sites allowing examination of age incidence curves of second neoplasms of the same organ. We considered the risk of second primary cutaneous malignant melanoma (CMM) in a population-based series of 3,439 first CMM registered and followed-up between 1974 and 2003 in the Swiss Cantons of Vaud and Neuchâtel (about 786,000 inhabitants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
1
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 15 publications
2
35
1
1
Order By: Relevance
“…While the relative risks of the major measures of personal sun exposure for multiple primary melanomas are similar to those for a first or any melanoma, the absolute risks conferred by equivalent levels of exposure will be quite different, because the absolute risk of a subsequent melanoma in a person who has already had a melanoma is some 2-4 times greater than that of a first melanoma in an otherwise similar person [1,17]. Minimizing sun exposure might, therefore, be of particular value in reducing risk of multiple primary melanomas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the relative risks of the major measures of personal sun exposure for multiple primary melanomas are similar to those for a first or any melanoma, the absolute risks conferred by equivalent levels of exposure will be quite different, because the absolute risk of a subsequent melanoma in a person who has already had a melanoma is some 2-4 times greater than that of a first melanoma in an otherwise similar person [1,17]. Minimizing sun exposure might, therefore, be of particular value in reducing risk of multiple primary melanomas.…”
Section: Discussionmentioning
confidence: 99%
“…People who have had one melanoma have an important risk of a second, estimated at an average of 1% a year [1]. Studies of risk of multiple primary melanomas have been concerned mainly with influences of the previous history of melanoma, presence of dysplastic nevi, or possible genetic susceptibility [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…While surveillance is obviously motivated by the risk of recurrence, this risk diminishes within a few years of diagnosis [13]. Two studies, however, have found that the risk of a second primary melanoma does not decline with time [11,14].…”
Section: Introductionmentioning
confidence: 97%
“…Risk of a second primary cutaneous melanoma among melanoma patients is found to be 6.01 per 1,000 person years after analysis of 20 years of follow-up in Queensland from 1982(McCaul et al, 2008. Analysis of a Swiss registry found the 20-year incidence of second primary melanoma to be 5% (Levi et al, 2005). A retrospective study of patients with multiple primary melanomas identified several risk factors for multiple melanomas such as early age at diagnosis, dysplastic nevi (diagnosed clinically or histologically), family history of dysplastic nevi or melanoma, and history of dysplastic nevus with a family history of melanoma (Stam-Posthuma et al, 2001).…”
Section: Personal History Of Skin Cancermentioning
confidence: 99%